2022
DOI: 10.1186/s12882-021-02653-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the MEST score for prognostic staging in IgA nephropathy

Abstract: Background The Oxford classification/MEST score is an established histopathologic scoring system for patients with IgA nephropathy (IgAN). The objective of this study was to derive a prognostic model for IgAN based on the MEST score and histopathologic features. Methods A total of 306 patients with biopsy-proven primary IgAN were included. Histopathologic samples were retrieved from the Norwegian Kidney Biopsy Registry and reclassified according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Even though the tools are available online, clinicians still must provide both clinical and histopathologic data to use them. As described previously, we found that the MEST score alone performed well as a prognostic model [ 19 ]. This finding could indicate that some clinical parameters, such as blood pressure, proteinuria, and eGFR, fluctuate, which makes them, to some extent, less accurate than histopathologic parameters, given a representative biopsy specimen.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Even though the tools are available online, clinicians still must provide both clinical and histopathologic data to use them. As described previously, we found that the MEST score alone performed well as a prognostic model [ 19 ]. This finding could indicate that some clinical parameters, such as blood pressure, proteinuria, and eGFR, fluctuate, which makes them, to some extent, less accurate than histopathologic parameters, given a representative biopsy specimen.…”
Section: Discussionsupporting
confidence: 60%
“…chose to add race to their model and leave out crescents, arguing that crescents are strongly associated with race, and race is a more prominent predictor of ESRD [ 23 ]. We have previously described that even though crescents are independently a strong predictor for progressive decrease in renal function [ 24 ], adding C to the MEST score does not significantly improve its prognostic value [ 19 ]. Notably, the ANN model includes sex as a prognostic factor, which is supported by a recent study describing male sex as a risk factor for IgAN [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the T score of the Oxford classification was associated with urinary Gd-IgA1 levels. Previous reports indicated that the T score is associated with a poor renal outcome [ 28 , 29 ]. Of note, the T score was significantly associated with the renal outcome, independently of clinical data [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Oxford MEST-C classification, a histopathologic tool assessing mesangial hypercellularity (M), endocapillary hypercellularity (E), segmental glomerulosclerosis (S), tubular atrophy/interstitial fibrosis (T), and cellular/ fibrocellular crescents (C), 16 was documented at baseline from pathology reports. In addition, the degree of complement staining was also documented from pathology reports, if available.…”
Section: End Pointsmentioning
confidence: 99%